The role of glucomannan fiber in childhood functional constipation - Indiana Aulia; Supriatmo Supriatmo; Emil Azlin; Atan Baas Sinuhaji (Indonesian Pediatric Society, 2016)
its most common type is functional constipation. The dietary fiber may be useful in childhood functional constipation management, but unfortunately the role of fiber in functional constipation is still less developed.Objective To determine the role of glucomannan in treatment of childhood functional constipation.Methods A crossover randomized controlled trial (RCT) was done from May until July 2012 in a boarding school in Medan, North Sumatera. The subjects were children with functional constipation aged 7 to 12 years. Subjects were randomised into two group receiving glucomannan fiber as polysaccharide gel (group A) and maltodextrin as placebo (group B) with each dose of 100 mg/kg/day (maximum of 5 g/day) diluted in 50 ml water/500 mg for 4 weeks, then after a wash out period we did the crossover of the two groups. Frequency and consistency of stools were recorded into diary sheet for 4 and 8 weeks of treatment. Functional constipation has been diagnosed based on Rome III criteria. Data was analyzed using independent T-test and Chi-square test.Results A total of 36 subjects were eligible with each group consisting of 18 subjects and mean of weight of 25 kg. We found significant difference in stool frequency, treated on glucomannan with P= 0.002 before and P = 0.0001 after the wash out period. For stool consistency, we found difference while treated on glucomannan 9/18 (P= 0.034) in 4 weeks before and 11/18 (P = 0.008) in 4 weeks after the wash out period.Conclusion Glucomannan has significant effect to improve functional constipation especially in 4 weeks treatment.